Longitudinal Associations Among Service Members' PTSD Symptoms, Partner Accommodation, and Partner Distress. Issue 6 (November 2022) - Fredman, Steffany J.; Le, Yunying; Renshaw, Keith D.; Allen, Elizabeth S.
Highlights: Partners accommodate PTSD by changing their behaviors in response to symptoms. We investigated links between accommodation and partner distress over time. PTSD symptoms predict increases in partner depression through accommodation. Partners who accommodate more are more depressed if accommodating to avoid conflict. Partners who accommodate more are less relationally satisfied. Abstract: Romantic partners' accommodation of trauma survivors' posttraumatic stress disorder (PTSD) symptoms (e.g., participating in avoidance and safety behaviors, not expressing one's thoughts and feelings) is a putative mechanism linking PTSD symptoms and partner distress, but this hypothesis has never been empirically tested. The current study investigated this proposed within-couple mediation process from service members' PTSD symptoms to partners' depressive symptoms and relationship satisfaction through partner accommodation, as well as between-couple associations among these constructs and the possible moderating role of partners' conflict avoidance and helplessness (CAH) motivations for accommodating service members' PTSD symptoms. We examined these questions in 272 male service member/female civilian couples assessed four times over an 18-month period using the multiple-group version of the random intercept cross-lagged panel model. Within couples, service members' higher levels of PTSD symptoms at one time point significantly predicted partners being more accommodating at the next time point (βs = .14–.19), which, in turn, significantly predicted higher levels of partner depressive symptoms at the subsequent time point (βs = .09–.19) but did not predict partners' subsequent relationship satisfaction. At the between-couple level, partner accommodation was significantly positively associated with partners' depressive symptoms only among those endorsing high CAH motivations for accommodation ( r  = .50). In addition, accommodation was significantly negatively associated with partners' relationship satisfaction regardless of CAH motivation level ( r s = −.43 to −.49). These findings are discussed in light of the potential for couple-based treatments for PTSD to enhance partner individual and relational well-being.